Durability Improvement of Synthetic Dry Adhesives by Metal Coatings - Gyuhe Kim; Taechang Ahn; Hui Yun Hwang (Advances in Materials Science and Engineering)
Gecko-like synthetic dry adhesives (SDAs) have adhesion comparable to that of a real Gecko’s foot, but with very low durability. To address this problem, self-cleaning or stiff core embedding methods have been proposed. However, the proposed methods require special locomotion or complicated manufacturing. In this study, we suggested a metal coating on synthetic dry adhesives to improve durability. SDAs were fabricated via PDMS. Then, metals such as indium, zinc, and gold were coated on the SDAs. The adhesion tests show that the indium- and zinc-coated microstructures have a higher shear adhesion strength than the noncoated ones. Also, the shear adhesion strength of noncoated SDAs was only 14.5% of the initial strength while that of the zinc-coated ones was 35.6% after 200 times of attachment and detachment. We could find PDMS debris and fractures on noncoated SDAs, which results in weakening of the adhesion strength. On the other hand, a relatively high hardness, strength, and stiffness of the zinc coating layers reduced the wear and fractures of the micropatterns, which led to an improved durability in the SDAs. From these tests, we can conclude that the metal coating method could improve the durability of the SDAs.